The Effect Of Stocking Density and Feeding Frequency On Growth and Survival Rate Of Hard-Lipped Barb Larvae (Osteochilus hasselti C.V.) - Nicolas Maruli S; Netti Aryani; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe aim of this research was to determine the effect of stocking density and feeding frequency on growth and survival rate of hard-lipped barb larvae. This research was conducted from July-August 2018 at Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty Riau University. The Method used is a Factorial Completely RandomizedDesign with two factors, the first factor is stocking density with three levels namely 3 larvae/L (T3), 5 larvae/L (T5) and 7 larvae/L (T7). While the second factor is feeding frequency 2 times/day (F2) and 4 times/day (F4).To minimize errors, each level of treatment was repeated 3 times. The result showed that stocking density and feeding frequency were significant on absolute weight, absolute length, average growth rate, survival rate and feed efficiency. The treatment T3F4 (3 larvae/L and feeding frequency 4 times/day) was resulted the highest value with an absolute weight of 1,58 gr, absolute length 3.72 cm, average growth rate of 14.09 %/day, feed eficiency 19 % and survival rate 91,11 %. The water quality parameters during research was in optimal range temperature 25,3-27,8°C, pH 5,1-6,5 and dissolved oxygen 4,1-5,2 mg/l. Keywords : Stocking denstity, Feeding frequency, Growth, and Survival rate